Obtenção de complexos de Pt(II) e Pd(II) derivados de 1,3,4-oxadiazol-2-(3H)-tiona e 5-amino-1,3,4-tiadiazol-2-tiol: potencial antitumoral de dois complexos de Pt(II) contendo 1,10-fenantrolina - Souza, Wesley Almeida (2021)
Metal-based drugs have been developed in order to minimize side effects and/or to overcome intrinsic or acquired resistance to antitumor drugs available in medical clinics. In this sense, we are also looking for new pharmacological agents capable of curing or at least prolonging the survival of patients with tumors classified as incurable until then. Considering the need for rational production of new antitumor agents, this work describes the synthesis and structural characterization of new complexes of Pt (II) and Pd (II) of the type [M(L1)2(L2)2] (L1 = derived from 5-alkyl-1,3,4-oxadiazole-2-thione (5-alkyl-odztH) and L2 = triphenylphosphine) and of the type [M(L1)2L2] (L1 = derived from 5-alkyl-odztH or 5-amino-1,3,4- thiadiazole-2-thiol (5amino-tdztH) and L2 = 1,10- phenanthroline). The platinum and palladium complexes were characterized by elemental analysis, conductivity measurements, high-resolution electrospray ionization mass spectrometry (HRESIMS), infrared spectroscopy (FT-IR) and multinuclear NMR spectroscopy. Three complexes of the type [Pt(L1)2(PPh3)2] and one complex of the type [Pt(L1)2fen] had their crystalline structures determined by single-crystal X-ray diffraction. In all the complexes, the metal ion was coordinated with the two L1 ligands via a sulfur atom, in which two triphenylphosphine molecules or one phenanthroline molecule completes its coordination sphere. The molar conductivity values of 1.0 × 10−3 mol L−1 solutions confirm that the complexes are non-electrolytes. The cytotoxic activity of the [Pt(heptyl-odzt)2fen] and [Pt(nonyl-odzt)2fen] complexes was evaluated in two tumor-cell lines (MCF 7 and MDA MB 231), with the complex [Pt(5 nonil odztH)2fen] being more active in both, since their IC50 values were lower. DNA interaction studies for both complexes reveled Kb values on the order of 104 M−1, with no variation observed in positive or negative bands of circular dichroism (CD) spectra. In turn, in the fluorescence spectra of the Hoechst-DNA system, an observed reduction in fluorescence intensity indicated that these complexes interact with DNA through the minor groove. These observations are in line with what is expected for compounds with lipophilic properties, as it is observed that there is a significant improvement both in cytotoxic activity and in the interaction with DNA, of the complex whose ligand has a larger aliphatic chain.